Gilles Deleuze: Schizo-analysis vs. Dialectical Materialism. Part I.: Savages, Barbarians and Civilized: dialectical processes or machinic processes? (Tábano, 2025)
This monographic study (which is divided into two articles that will be published consecutively in this Journal) is dedicated to studying the way in which Gilles Deleuze approached the psycho-political problem of male domination and male psycho-sex-political violence. To do so, it will be necessary to start from the question that questions the genetic relationship that the Patriarchy (as a mega-network of male alliances of sex-power) has with the State (as a way of organizing human sociability) and with Capitalism (as a way of organizing human productivity). Around this genetic relationship, Deleuze will postulate, following the Marxist sinologist Ferenc Tökei, that the ‘freed slave’ (ancestor of the modern proletarian) was the key male social personification in the patriarchal genesis of Capitalism by the State, with the psycho-sexual exploitation of women (prostitution) being a first-order enterprise for the understanding of this genesis. According to Schizo-analysis, psycho-sexual and libidinal exploitation is the ratio of economic exploitation and class domination. Therefore, we cannot address this genetic relationship between Patriarchy, State and Capital (regarding male violence) without addressing, in this “Part I”, the Deleuze/Guattari’s critiques to Marx/Engels: acratic schizo-analysis (as an analysis of machine processes) versus dialectical materialism (as an analysis of dialectical processes). Now, is dialectical materialism operative (in the Critic and in the Clinic) when it comes to understanding and characterizing (and fighting against) male psycho-sexual violence, such as prostitution? How did Marx, Engels, Bebel and Riazánov characterize (from dialectical materialism) the prostitution, the prostitute, and the trick/john? Don’t they end up incurring in an economic and exchanger reductionism (in sexual matters) that turns invisible the patriarchal causes of male domination and violence, even becoming its unsuspected guarantor “from the left”? This will be the central problem of “Part II”. Our social concept of ‘Mental Health’ depends directly on the way of characterizing these psycho-sexual political problems.
Keywords: Patriarchy; Psycho-sexual domination; Freed slave; Marxismus; State; Capital